Augmentation of Turbulent Flow Heat Transfer in A Horizontal Tube with Varying Width Twisted Tape Inserts - Sarad, S. Naga; Raju, A.V. Sita Rama; Radha, K. Kalyani; Sunder, L. Syam (Universiti Malaysia Pahang, 2012)
The present work shows the results obtained from experimental investigations of the augmentation of turbulent flow heat transfer in a horizontal tube by means of varying width twisted tape inserts, with air as the working fluid. In order to reduce excessive pressure drops associated with full-width twisted tape inserts, with a lower corresponding reduction in heat transfer coefficients, reduced-width twisted tapes of widths ranging from 10 mm to 22 mm are used, which are lower than the internal diameter of the tube of 27.5 mm. Experiments were carried out for plain tubes with/without twisted tape inserts at a constant wall heat flux and different mass flow rates. The twisted tapes are of three different twist ratios (3, 4 and 5), each with five different widths (26 (full-width), 22, 18, 14 and 10 mm). The Reynolds number varied from 6000 to 13500. Both the heat transfer coefficient and pressure drop are calculated, and the results are compared with those of a plain tube. It is observed that with the inclusion of twisted tape inserts there is a significant increase in the heat transfer coefficients. Correlations are developed for friction factors and Nusselt numbers for a fully-developed turbulent swirl flow, which are applicable to full-width as well as reduced-width twisted tapes, using a modified twist ratio as the pitch to width ratio of the tape.